2022
DOI: 10.3389/fphys.2022.805861
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference Analysis Reveals the Positive Regulatory Role of Ferritin in Testis Development in the Oriental River Prawn, Macrobrachium nipponense

Abstract: Ferritin plays an essential role in organismic and cellular iron homeostasis in Macrobrachium nipponense. In this study, we aimed to investigate the role of ferritin in the sexual development of male M. nipponense. According to the qPCR analysis of different tissues and developmental stages, ferritin exhibited high expression levels in the testis and androgenic gland, from post-larval developmental stage 5 (PL5) to PL15, indicating that it may be involved in gonad differentiation and development, especially in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In male crustaceans, the androgenic gland and testis are the main reproductive organs (Sagi et al, 1986;Sagi and Cohen, 1990;Qiu et al, 1995). In the current study, DIG signals were observed in the ejaculatory bulb that surrounds the androgenic gland but not in androgenic gland cells, indicating that CycA did not directly involved in process of sex determination and differentiation in M. nipponense, while it played essential roles in the formation and maintenance of the normal structure of the androgenic gland (Jin et al, 2018;JinC et al, 2021;Jin et al, 2022). In the testis, DIG signals were only observed in the spermatogonia, indicating that CycA was involved in the process of spermatogenesis in M. nipponense, especially that of the spermatogonia proliferation (JinC et al, 2021;Jin et al, 2022).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In male crustaceans, the androgenic gland and testis are the main reproductive organs (Sagi et al, 1986;Sagi and Cohen, 1990;Qiu et al, 1995). In the current study, DIG signals were observed in the ejaculatory bulb that surrounds the androgenic gland but not in androgenic gland cells, indicating that CycA did not directly involved in process of sex determination and differentiation in M. nipponense, while it played essential roles in the formation and maintenance of the normal structure of the androgenic gland (Jin et al, 2018;JinC et al, 2021;Jin et al, 2022). In the testis, DIG signals were only observed in the spermatogonia, indicating that CycA was involved in the process of spermatogenesis in M. nipponense, especially that of the spermatogonia proliferation (JinC et al, 2021;Jin et al, 2022).…”
Section: Discussionmentioning
confidence: 58%
“…The tissues were fixed in paraformaldehyde (4%) (Sangon, Shanghai, China), and then they were embedded in paraffin and sliced into 4 µm thick sections for the analysis. Details about the primer design and in situ hybridization can be found in previous reports ( Jin et al, 2018 ; Li et al, 2018 ; Jin et al, 2022 ). Briefly, the specific anti-sense (experimental group) and sense (control group) probes were designed using Primer5 software based on the cDNA sequence of Mn-CycA .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferritin, gem‐associated protein 2‐like isoform X1 ( GEM ), and DNA polymerase zeta catalytic subunit ( Rev3 ) were differentially expressed in the proteomic profiling analysis of the androgenic gland between the reproductive and the nonreproductive seasons 50 . RNAi analysis showed that ferritin and rev3 had positive regulatory roles in testis development in M. nipponense through positive regulation of the expression of IAG and the secretion of testosterone, 88,89 whereas GEM had negative effects 90 …”
Section: Gene Functional Analysismentioning
confidence: 99%
“…86,87 Ferritin, gem-associated protein 2-like isoform X1 (GEM), and DNA polymerase zeta catalytic subunit (Rev3) were differentially expressed in the proteomic profiling analysis of the androgenic gland between the reproductive and the nonreproductive seasons. 50 RNAi analysis showed that ferritin and rev3 had positive regulatory roles in testis development in M. nipponense through positive regulation of the expression of IAG and the secretion of testosterone, 88,89 whereas GEM had negative effects. 90 RNAi analysis revealed that DMRT11E positively regulated the expression of vitellogenin, while its regulatory effect on IAG was negative, indicating that DMRT11E negatively regulates male sexual development in M. nipponense.…”
Section: Ferritinmentioning
confidence: 99%